Serverless security : understand, assess, and implement secure and reliable applications in AWS, Microsoft Azure, and Google Cloud /: understand, assess, and implement secure and reliable applications in AWS, Microsoft Azure, and Google Cloud. ([2020]) - Calles, Miguel A
No abstract available